2005
DOI: 10.3748/wjg.v11.i32.5075
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty with diagnosis of malignant pancreatic neoplasms coexisting with chronic pancreatitis

Abstract: Chronic pancreatitis is a relatively common disease. We enco un tered tw o d if f erent c a s es o f bel atedly demonstrated pancreatic carcinoma featuring underlying chronic pancreatitis. The first case was one that was highly suspected as that of a malignancy based upon imaging study, but unfortunately, it could not be confirmed by intra-operative cytology at that time. Following this, the surgeon elected to perform only conservative bypass surgery for obstructive biliary complication. Peritoneal carcinomato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…25 Markers for pancreatic cancer have been identified; serum CA19-9 is regarded as a reliable test for the detection of pancreatobiliary malignancy but does not reliably detect early, small, pancreatic cancers. 26 As far as we are aware, the present study is the first to demonstrate a relationship between the clinicopathological characteristics of pancreatic carcinoma and the prognostic significance of LAPTM4B-35 protein through semiquantitative immunohisto chemistry. LAPTM4B-35 protein was present in a large percentage of pancreatic carcinoma tissue samples and high LAPTM4B-35 staining was significantly correlated with tumour stage, degree of differentiation and pathological stage, but not with age, gender, metastasis or node stage, tumour location vascular invasion or serum CA19-9 level.…”
Section: Discussionmentioning
confidence: 60%
“…25 Markers for pancreatic cancer have been identified; serum CA19-9 is regarded as a reliable test for the detection of pancreatobiliary malignancy but does not reliably detect early, small, pancreatic cancers. 26 As far as we are aware, the present study is the first to demonstrate a relationship between the clinicopathological characteristics of pancreatic carcinoma and the prognostic significance of LAPTM4B-35 protein through semiquantitative immunohisto chemistry. LAPTM4B-35 protein was present in a large percentage of pancreatic carcinoma tissue samples and high LAPTM4B-35 staining was significantly correlated with tumour stage, degree of differentiation and pathological stage, but not with age, gender, metastasis or node stage, tumour location vascular invasion or serum CA19-9 level.…”
Section: Discussionmentioning
confidence: 60%
“…However, carbohydrate antigen 19–9 (CA 19–9) is still currently the only serum biomarker which has been widely used for detection of PDAC; however, this approach is frustrating in regard to both specificity and sensitivity . It is reported that 40% of chronic pancreatitis (CP) patients and 70% benign biliary obstruction (BBO) patients have elevated CA19‐9 levels, making it difficult to discriminate PDAC from CP or BBO. Hence, the efficiency of CA19‐9 reduced but we can complement the specificity and sensitivity of CA19‐9 in combination with other biomarkers …”
mentioning
confidence: 99%
“…Inflammatory processes or necrosis of these organs can release significant amounts of CEA and its concentration may raise above the URL. High concentrations of this TM have been reported in pancreatitis [112], diverticulitis [113], and peptic ulcer [114], where the levels may rise to up to four or five times the URL. Inflammatory bowel disease has been associated with an increased number of false positives, reaching values four to eight times the URL in severe cases [115].…”
Section: Carcinoembryonic Antigen (Cea)mentioning
confidence: 98%